2023
DOI: 10.1242/jeb.245453
|View full text |Cite
|
Sign up to set email alerts
|

Crows protect visual working memory against interference

Abstract: Working memory, the ability to actively maintain and manipulate information across time, is key to intelligent behavior. Due to the limited capacity of working memory, relevant information needs to be protected against distracting representations. Whether birds can resist distractors and safeguard memorized relevant information is unclear. We trained carrion crows in a delayed match-to-sample task to memorize an image while resisting other, interfering stimuli. We found that the repetition of the sample stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In these studies, only complex pictures were used as stimuli and thus, the impact of stimulus complexity has not been investigated with electrophysiological methods. However, in a behavioral study, the interfering impact on working memory was shown to be small for simple distractor stimuli and more severe for complex pictures, hinting towards differential processing of both stimulus classes 41 . To systematically investigate interfering effects of the different stimulus classes, an experiment as performed by Wright et al 42 would be needed.…”
Section: Discussionmentioning
confidence: 97%
“…In these studies, only complex pictures were used as stimuli and thus, the impact of stimulus complexity has not been investigated with electrophysiological methods. However, in a behavioral study, the interfering impact on working memory was shown to be small for simple distractor stimuli and more severe for complex pictures, hinting towards differential processing of both stimulus classes 41 . To systematically investigate interfering effects of the different stimulus classes, an experiment as performed by Wright et al 42 would be needed.…”
Section: Discussionmentioning
confidence: 97%
“…When the cue is highly indicative of target position, the crows may learn to associate cue and target side to improve task-relevant performance, in this case detection speed. Crows have substantial working memory capacity [34][35][36][37][38] and are able to learn associations between abstract stimulus features even across modalities [39][40][41], enabling them to guide behaviour using associative stimuli. Similarly, barn owls show faster RTs to valid than to invalid visual cues with 80% validity in a sound localization task at SOAs of 500-1000 ms [6].…”
Section: Central Associative Cueingmentioning
confidence: 99%